GROWTH PERFORMANCE, CARCASS YIELD AND HAEMATOLOGICAL RESPONSE OF BROILER CHICKENS FED ON PROCESSED HARICOT BEAN (Phaseolus vulagris L.) - HEMACHA, SELAMU ABRAHAM; LOMBEBO, WONDIMU AYELE (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Background: Haricot bean is among the most important legumes grain in Ethiopia. The beans are good sources of protein, carbohydrates and mineral nutrients required for normal functioning of the body. Despite of its nutritional quality, it is poor digestible due to anti-nutritional factors present in the bean. Methods: A total of 168 Sasso strain broiler chickens were used with an initial body weight of 39.65±2.15g for the trial. The chicks were randomly allotted into four treatments with 14 birds per replication. Haricot bean was soaked in water for five hours at ratio of 1 kilogram to 5 liters, and then cooked for an hour to reduce anti-nutritional factors. The treatment diets have contained the bean at proportion of 0, 10, 20 and 30% for T1, T2, T3 and T4, respectively. Results: T3 and T4 gave best performance (P≤0.05) in final body weight, slaughter weight, dressed carcass and eviscerated weight. A significant (P≤0.05) increase were observed in white blood cell, red blood cell, haemoglobin and packed cell volume with increasing the rate of processed haricot bean in the treatment diets.. Conclusions: Therefore, an amalgamation of processed haricot beans in the broiler ration showed an optimistic result in the overall performance and immunity of broiler chickens.